2018
DOI: 10.3390/ma11081448
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Hybrid Ultra-High Performance Engineered Cementitous Composites Incorporating Steel and Polyethylene Fibers

Abstract: This paper presents the authors’ newly developed hybrid ultra-high performance (HUHP) engineered cementitious composite (ECC) with steel (ST) and polyethylene (PE) fibers. From this point on it will be referred to as HUHP-ECC. The volumes of steel and PE fibers were adjusted to obtain different mechanical properties, including compressive strength, tensile, and flexural properties. We found that tensile and flexural properties, including bending strength and ductility indexes, increased with higher PE fiber am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(22 citation statements)
references
References 39 publications
2
18
0
2
Order By: Relevance
“…Figure 8 shows the direct tensile stress-strain curves of the RULCC coupon specimens. It is found that the tensile strain capacity of R0-0.7PE with low fiber content of 0.7% can reach 3%-4%, which is much higher than that of normal concrete, and meets the tensile strain requirements of the Engineered Cement Composite (ECC) materials [41]. The tensile strain capacity of R10-0.7PE with 10% rubber powder can reach about 4%-5%, showing promising ductile performance.…”
Section: Static Tensile Testmentioning
confidence: 87%
“…Figure 8 shows the direct tensile stress-strain curves of the RULCC coupon specimens. It is found that the tensile strain capacity of R0-0.7PE with low fiber content of 0.7% can reach 3%-4%, which is much higher than that of normal concrete, and meets the tensile strain requirements of the Engineered Cement Composite (ECC) materials [41]. The tensile strain capacity of R10-0.7PE with 10% rubber powder can reach about 4%-5%, showing promising ductile performance.…”
Section: Static Tensile Testmentioning
confidence: 87%
“…They have attracted the increasing attention of researchers and engineers to a wide range of innovative applications in structural engineering due to their advantageous mechanical properties and durability [1][2][3][4][5][6][7][8][9][10][11]. Engineered Cementitious Composites (ECC), a unique class of HPFRCCs, feature a large strain capacity with selfcontrolled crack width [12][13][14][15][16][17][18][19][20][21][22][23]. Its tensile strain capacity can reach more than 3% [17][18][19][20][21][22][23][24][25][26], and its average crack width was reported to be less than 60 µm when the tensile strain demand was less than 1% [14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the addition of steel fiber can improve the tensile strength, impact resistance and toughness of concrete, but steel fiber has the disadvantages of easy corrosion, high bulk density, poor performance and so on. Polypropylene fiber can improve the tensile capacity and deformation capacity of concrete, but the elastic modulus and compressive capacity of concrete usually decrease slightly [4]. Mixing two or more kinds of fibers into concrete to make hybrid fiber concrete can effectively solve the above problems, and has better economic benefits [5].…”
Section: Introductionmentioning
confidence: 99%